Integral assessment of football team tactics - Viktor Kostiukevych; Natalia Shchepotina; Vadym Adamchuk; Beatrice Abalașei; Tetiana Vozniuk; Viktoriia Bohuslavska; Andrii Drachuk; Artem Mezhvynskyi (Kharkiv State Academy of Physical Culture, 2023)
The purpose of the research was to develop a methodology of control and determine the indicators of integral assessment of competitive performance by various tactical game models of highly qualified football club teams. Material and methods. In the period of 2018-2023, 110 games of the leading European club teams and 46 games of the football team "Dynamo" (Kyiv) were analyzed with regard to the tactical models of the games "A", "B", "C", "D". Specific coefficients were determined in the phase of passing and possession of the ball, which constituted an integral assessment of competitive performance. The assessment of attacks and goalscoring situations, the realization of pressing, the effectiveness of players' interaction in the phase of picking up the ball, as well as the criteria of creativity and game combinations were taken into account. Results. An integral assessment methodology of the competitive performance of football club teams has been developed, consisting of 10 specific coefficients: high pressing coefficient; high pressing efficiency factor, low pressing efficiency factor, coefficient of ball picking efficiency, ball interceptions efficiency coefficient, penetration attack efficiency coefficient, successful penetration attack efficiency coefficient, goalscoring situation coefficient, the creativity and the combinability coefficients. The first five coefficients characterize the team's play in the phase of picking up the ball, the other five - in the phase of ball control on the field. The determined indicators of the integral assessment of the competitive performance of the leading European club teams according to different tactical models of the game are as follows: model "A" - 5.95±0.32 points; model "B" - 5.35±0.29 points; model "C" - 5.57±0.47 points; model "D" - 5.14±0.33 points. Conclusions. The integral assessment of competitive performance allows to provide effective control of interaction of players of a club football team in the phases of picking up and possession of the ball.